Awareness and Implementation of Consumer Protection Law in the Service Sector of Tomohon : Kesadaran dan Implementasi Undang-Undang Perlindungan Konsumen di Sektor Jasa Kota Tomohon - Shintia Alvernia Gorrettie Gijoh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the implementation of consumer protection law within service businesses in Tomohon City, focusing on the extent to which business operators understand and apply Law No. 8 of 1999 concerning Consumer Protection. The main objectives of the study are to assess the level of legal awareness among service business operators, identify the forms of consumer protection provided, and analyze the barriers to effective implementation. The research also explores the mechanisms used by businesses to resolve consumer disputes and the occurrence of consumer rights violations. This study employs a descriptive quantitative approach with a survey methodology, using a structured questionnaire distributed to 30 service business operators in various sectors, including tourism, culinary, and domestic services. The findings reveal that the majority of respondents possess a moderate level of understanding of the consumer protection law, with a significant gap in the application of more comprehensive consumer protection measures such as service guarantees and compensation. Additionally, internal mediation is the most commonly used dispute resolution mechanism, while formal channels such as the Consumer Dispute Settlement Agency (BPSK) and legal intervention are underutilized. The study also highlights significant barriers to effective implementation, including limited supervision and a lack of legal awareness among business operators. The absence of formal consumer complaint channels in many businesses further exacerbates the situation, leading to an environment of limited accountability. The implications of this study emphasize the need for increased legal education and training for service business operators, particularly in the informal sector. Government and civil society organizations must collaborate to enhance legal literacy and facilitate better consumer protection practices. Future policy recommendations include simplifying legal procedures and strengthening consumer protection institutions to foster a more equitable and transparent service economy in Tomohon.